Male gametogenesis in flowering plants - Cui, Dan-Lu; Xu, Chun-Xia; Wang, Ping; Gao, Tian-Ying; Wang, Bo; Yu, Tian-Ying (Frontiers in Sustainable Food Systems, 2024)
The life cycles of plants are characterized by significant alternations between the diploid sporophytic and the haploid gametophytic generations. Meiosis and fertilization are the prerequisites for achieving the alternation of generations. Diploid sporophytes undergo meiosis to produce haploid gametes, and male–female gametes fuse (double fertilization) to revert to the diploid sporophyte. The formation and development of male gametophytes are crucial for the alternation of generations in higher plants. During the long evolution of plants from aquatic to terrestrial, the way of sexual reproduction has undergone subversive innovations. From sperm swimming for fertilization to relying on the precise delivery of pollen tubes to female gametes for the fusion of the male–female gametes, higher requirements are placed on the male gametophytes’ development and fertilization process. The formation of male gametophytes has undergone significant changes to meet the needs for delivery and transportation of the male gametes. With the emergence of more and more evidence, the molecular mechanism underlying male gametophytes’ development, especially the initiation and specialization of germline cells has been better understood. Focusing on the latest studies, we reviewed and elucidated the critical proteins and factors involved in male gametophyte formation, highlighting the decisive role of auxin in archesporial cell specialization and the importance of microspore maturation in pre-mitosis, and analyzed the molecular mechanisms underlying male gametogenesis, with a view to providing insights for further exploration of male gametophytes formation in the future.